KEMANDIRIAN PETANI TERHADAP PEMANFAATAN JERAMI PADI SEBAGAI PUPUK BOKASHI PADA TANAMAN PADI DI KECAMATAN MANONJAYA KABUPATEN TASIKMALAYA - Rury Januari Ramdhan; Dedy Kusnadi; Harniati Harniati (Jurnal Inovasi Penelitian, 2020)
The use of organic fertilizers can maintain soil fertility so that paddy productivity will increase and be in line with sustainable farming systems. Paddy straw contains organic material which is good for soil fertility, so it can be used as one of the main organic fertilizer materials; one of them is bokashi fertilizer. Farmers are said to be independent if they can utilize the available resources optimally. Some farmers in Margahayu Village are still said to be less independent in processing straw into bokashi fertilizer so productivity does not increase. The purpose of this study is to measure the extent of the independence of farmers in using straw as bokashi fertilizer and the factors that influence it. This study shows that the independence of farmers is in the medium category and the factors that influence the independence of farmers include (1) length of farming, (2) selection of extension media, and (3) access to information on agricultural extension workers.